(untitled) (Research, Society and Development, 2021)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder that can compromise communication verbally or nonverbally with manifestation of repetitive movements and moments of distancing from contact with reality. Thus, it is essential to include physical therapy treatment early to develop the functions of routine activities, as well as improving the evolution of the development of coordination and interpersonal interaction. The aim of this work is to discuss the importance of the physical therapist professional’s role in the care of people with Autism Spectrum Disorder. This is a narrative literature review. For this article were made manual searches on the Platform Google Scholar and selected articles relevant to the theme for the composition of references. From the data presented it is identified that the role of the physiotherapist in the care of people with ASD is to enable both motor and mental improvements based on techniques that stimulate proximity to the patient dialogue, social integration and work of independence of the patient in a playful way. Thus, first as regards the motor establishment there is a communicative construction that defines the relationship of trust with the patient Finally, it is understood the importance of the physiotherapist’s role in the care of patients with ASD, given the need for motor and sensory stimuli. It is important to highlight the need for early intervention for better responses to treatment and adaptation to space. In this way, the evolution in the motor and sensorial aspects helps to improve the quality of life and social integration of the individuals.